MODEL-MODEL PEMBELAJARAN DAN PEMEFOLEHAN BAHASA KEDUA/ASING - Hanna - Sundari (Pujangga: Jurnal Bahasa dan Sastra, 2015)
ABSTRACT Models of language learning and acquisition in the issue of second /foreign language learning and acquisition have not been discussed much so far. However, the concepts of how learners acquire and learn language are essential to know and understand by teachers/lecturers who involve in the field of practical language teaching. This article tries to give a description of both models of language in general and model of language learning and acquisition in regard to the nature, the position, and the types of models build upon the experts. The models of language learning and acquisition discussed are Tradisional Model, Levelt Model, Paul Nation Model, Swain Model, and ACCESS Model. Key word: model, learning and acquisition, second/foreign language ABSTRAK Model pembelajaran dan pemerolehan bahasa dalam kajian pemerolehan bahasa kedua/asing memang tidak terlalu banyak didiskusikan. Namun begitu, konsep mengenai bagaimana bahasa asing/kedua diperoleh dan dipelajari perlu diketahui dan dipahami oleh guru/dosen yang berkecimpung dalam dunia pembelajaran bahasa secara praktis. Paparan ini memberikan deskripsi mengenai model pembelajaran secara umum dan model pembelajaran dan pemerolehan bahasa kedua/asing dalam aspek pengertian, posisi dalam kajian pembelajaran bahasa kedua/asing dan macam-macam model yang diperoleh dari berbagai pandangan ahli. Model pembelajaran dan pemerolehan bahasa asing/kedua yang akan dibahas, diantaranya: Model Tradisional, Model Levelt, Model Paul Nation, Model Swain, dan Model ACCESS.   Kata kunci: model, pembelajaran dan pemerolehan, bahasa kedua/asing